TOLERANSI BERAGAMA MENURUT HUKUM ISLAM - Subhan Subhan (STIESNU Bengkulu, 2022)
AbstractReligious tolerance in Islam is an attitude of respect, letting, allowing opinions, views, beliefs, habits, behaviors, and so on that are different from behavior that follows the rules of their respective religions, where the people always respect and respect the behavior of others. because tolerance in Islam means very appreciative of attitudes and actions that prohibit their existence discrimination against other people who are different in a society. Islam is a religion that teaches humanity to always respect and tolerate others and maintain the sanctity and truth of Islamic teachingsKeywords : Islam, Religious, Tolerance AbstrakToleransi beragama dalam Islam merupakan suatu sikap menghargai, membiarkan, membolehkan berpendapat, berpandanganan, kepercayaan, kebiasaan, kelakuan, dan sebagainya yang berbeda asal perilaku yang mengikuti aturan agama masing-masing, di mana umatnya selalu menghargai, menghormati terhadap perilaku orang lain. oleh sebab Toleransi dalam agama Islam berarti sangat menghargai sikap dan perbuatan yang melarang adanya diskriminasi terhadap orang lain yang berbeda dalam suatu masyarakat. Islam sebuah agama yang mengajarkan kepada umat manusia untuk selalu menghormati serta toleransi terhadap sesama dan menjaga kesucian serta kebenaran ajaran Islam Keyword: Islam, Agama, Toleransi